Use of Digital Technologies in Secondary Schools in the City of Nampula - Mozambique - Guedes António Caetano (Foxton Books, 2018)
The article addresses an exploratory study that took place in May and June of 2017 in the fourteen public secondary schools in Nampula city, north of Mozambique. The study aimed to understand how digital technologies as a whole are used in the teaching and learning process of Nampula city secondary schools. In order to collect data in schools, it was used on-site observation and interviewed fifteen ICT teachers from the respective schools. In order to understand and validate the data, it was used the confrontation of the curricular objectives of the ICT discipline with the data collected in the schools, regarding not only the modality of teaching of the ICT discipline but also about the good practices of the teachers in what is refers to the use of educational software / learning objects in the teaching and learning process of other disciplines. The results indicate that despite the efforts of the Ministry of Education and Human Development to equip secondary schools with computers, interactive whiteboards and the Internet; 12 of 14 schools theoretically teach ICT for lack of computers, and there are even schools that do not teach the discipline. Therefore, the scenario is two groups of students who complete high public school with different amounts of subjects and without any practical knowledge of ICT that compromises the curricular objectives and consequently the quality of the graduated student.